Neural activation during anticipation of monetary gain or loss does not associate with positive subjective response to alcohol in binge drinkers - Pabon, Elisa (Drug Alcohol Depend, 2020)
BACKGROUND: Alcohol use disorder (AUD) remains an unresolved source of morbidity and mortality. Psychopharmacological challenge studies and neuroimaging experiments are two methods used to identify risk of problematic substance use. The present study combined these two approaches by examining associations between self-reported stimulation, sedation, liking or wanting more after a dose of alcohol and neural-based responses to anticipation of monetary gain and loss. METHODS: Young adult binge drinkers (N=56) aged 21-29, with no history of Substance Use Disorder completed five experimental sessions. These included four laboratory sessions in which they rated their subjective responses to alcohol (0.8 g/kg for men, 0.68 g/kg for women) or placebo, and a single functional magnetic resonance imaging session in which they completed a monetary incentive delay task. During the scan, we recorded neural signal related to anticipation of winning $5 or $1.50 compared to winning no money (WinMoney-WinZero), losing $5 or $1.50 compared to losing no money (LoseMoney-LoseZero), and winning $5 or $1.50 compared to losing $5 or $1.50 (WinMoney-LoseMoney), in reward related regions. RESULTS: There were no significant associations between subjective ratings of “Feel Drug Effect”, “Like Drug Effect”, “Want More”, stimulation or sedation following the acute alcohol challenge and neural activation in reward related regions during anticipation of monetary gain or loss. CONCLUSIONS: These results suggest that sensitivity of neural reward circuits is not directly related to rewarding subjective experiences from alcohol. Taken together with previous studies, the present findings indicate that the association between the subjective effects of drugs and reward-related brain activity depends on the drugs, tasks or subject samples under study.